An asphalt mixture and a method for producing the same
Patent Information
- Application Number
- CN202611055347.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-16
AI Technical Summary
传统沥青混合料普遍存在以下不足:高温条件下沥青软化,在车辆荷载反复作用下易产生车辙变形;低温环境中沥青脆化,温缩应力易引发开裂;水分渗入沥青-集料界面导致粘附失效,造成集料剥离与松散掉粒;长期交变荷载作用下产生疲劳开裂
[0037]This invention utilizes a dual coupling system consisting of diatomaceous earth-loaded titanate coupling agent and γ-aminopropyltriethoxysilane to establish a chemical bridge at the asphalt-aggregate-fiber multiphase interface, effectively preventing interfacial delamination caused by moisture intrusion and enhancing water damage resistance. Steel slag micropowder and nano-paleite are compounded to form a micro-nano multilevel filler, densifying the matrix, increasing modulus, and significantly enhancing high-temperature rutting resistance. Basalt short-cut fibers, after acid etching activation and silane grafting treatment, exhibit strengthened fiber-matrix interfacial bonding, resulting in significant fiber pull-out energy dissipation and bridging crack effects under load, effectively inhibiting low-temperature cracking and fatigue crack propagation. The synergistic effect of all components endows the mixture with excellent high-temperature rutting resistance, low-temperature crack resistance, water damage resistance, and fatigue durability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of asphalt mixture preparation technology, and in particular to an asphalt mixture and its preparation method. Background Technology
[0002] Asphalt mixtures, as the main material for road paving, directly affect road service life and driving safety. Traditional asphalt mixtures generally suffer from the following shortcomings: asphalt softens under high temperatures, easily causing rutting deformation under repeated vehicle loads; asphalt becomes brittle in low-temperature environments, and thermal shrinkage stress easily leads to cracking; moisture penetrates the asphalt-aggregate interface, causing adhesion failure, resulting in aggregate stripping and loosening; and fatigue cracking occurs under long-term alternating loads. Among existing modification methods, polymer modifiers have limited compatibility with asphalt, making it difficult to simultaneously achieve high and low temperature performance; while fiber reinforcement can improve crack resistance, the interface bonding between ordinary fibers and the asphalt matrix is weak, resulting in low stress transfer efficiency; single coupling agents have limited effect on improving interface bonding and cannot achieve multi-scale synergistic reinforcement between inorganic fillers, fibers, and organic asphalt matrix. Therefore, there is an urgent need to develop an asphalt mixture that can simultaneously improve high-temperature rutting resistance, low-temperature crack resistance, water damage resistance, and fatigue durability.
[0003] Therefore, this invention is proposed. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides an asphalt mixture and its preparation method. By strengthening the asphalt-aggregate interface bonding through a dual coupling system, densely reinforcing the matrix with composite micro-nano fillers, toughening and crack-resistant by surface-grafted basalt short-cut fibers, and softening modification with hydroxyl-terminated liquid nitrile rubber, the mixture simultaneously possesses excellent high-temperature rutting resistance, low-temperature crack resistance, water damage resistance, and fatigue durability.
[0005] In order to achieve the objective of this invention, the following technical solution is adopted:
[0006] This invention provides an asphalt mixture, comprising, by weight:
[0007] 4.5-6 parts of base asphalt;
[0008] 58-65 parts of coarse aggregate;
[0009] 18-25 parts of fine aggregate;
[0010] 6-10 parts of the first modified filler;
[0011] 3-6 parts of the second modified filler;
[0012] 0.25-0.45 parts of basalt short-cut fibers;
[0013] 0.5-1.2 parts of hydroxyl-terminated liquid nitrile rubber;
[0014] 0.08-0.15 parts of γ-aminopropyltriethoxysilane;
[0015] 4-8 parts of limestone mineral powder;
[0016] The first modified filler is a diatomaceous earth-supported titanate coupling agent, and the titanate coupling agent is isopropyltris(dioctylpyrophosphate) titanate.
[0017] The second modified filler is a composite powder of steel slag micro powder and nano-pachymanite, wherein the steel slag micro powder has a specific surface area of 450-550 m². 2 / kg, wherein the diameter of the nano-pachymanite is 20-40nm and the length is 0.5-5μm, and the mass ratio of the steel slag powder to the nano-pachymanite is 7:3;
[0018] The surface of the basalt short-cut fibers is acid-etched and activated, and then grafted with γ-aminopropyltriethoxysilane. The length of the basalt short-cut fibers is 3-6 mm.
[0019] Furthermore, in the diatomaceous earth-supported titanate coupling agent, the mass ratio of the titanate coupling agent to the diatomaceous earth is (0.15-0.25):1.
[0020] Furthermore, the first modified filler also includes sodium dodecylbenzenesulfonate, accounting for 0.5% of the total mass of the first modified filler.
[0021] Furthermore, the coarse aggregate is basalt crushed stone with a particle size ≥ 2.36 mm, and the fine aggregate is manufactured sand with a particle size < 2.36 mm.
[0022] Furthermore, it also includes 0.3-0.8 parts of modified polyacrylonitrile short fibers, wherein the modified polyacrylonitrile short fibers are polyacrylonitrile short fibers treated with hydrazine hydrate in a liquid phase. The conditions for the hydrazine hydrate liquid phase reduction treatment are: hydrazine hydrate mass fraction of 5%-10%, treatment temperature of 70-90℃, treatment time of 2-4 hours, and the length of the polyacrylonitrile short fibers is 2-5mm, and the diameter of the single filament is ≤10μm.
[0023] Furthermore, it also includes 0.1-0.3 parts of a layered bimetallic hydroxide and 0.2-0.6 parts of a hindered amine light stabilizer; the layered bimetallic hydroxide is a magnesium-aluminum type layered bimetallic hydroxide, wherein the molar ratio of Mg to Al is 2:1-3:1; the hindered amine light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0024] The present invention also provides a method for preparing the above-mentioned asphalt mixture, comprising the following steps:
[0025] After heating the base asphalt, add hydroxyl-terminated liquid nitrile rubber under stirring conditions and stir until homogeneous to obtain a mixture;
[0026] Add a first modified filler and part of a second modified filler to the mixture, stir evenly, then add γ-aminopropyltriethoxysilane, continue stirring and let stand to obtain modified asphalt binder;
[0027] The coarse aggregate and fine aggregate are dried and heated separately, then mixed evenly, and then the modified asphalt binder is added and mixed to obtain a mixture.
[0028] Add the remaining second modified filler and surface-treated basalt short-cut fibers to the mixture, continue to mix evenly, then add limestone mineral powder and mix evenly to obtain asphalt material;
[0029] The asphalt material is shaped, cooled, and then demolded.
[0030] Furthermore, the method for preparing the surface-treated basalt short-cut fibers is as follows:
[0031] Basalt chopped fibers were immersed in 1 mol / L hydrochloric acid solution for ultrasonic treatment, water washing, and drying. The dried basalt chopped fibers were then immersed in 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution and reacted at 60°C for 2 hours. After washing, the fibers were dried.
[0032] The preparation method of the diatomaceous earth-supported titanate coupling agent is as follows:
[0033] Isopropyl tris(dioctyl pyrophosphate) titanate was dissolved in anhydrous ethanol to prepare a coupling agent solution. The dried diatomaceous earth was added to the coupling agent solution and stirred for 2 hours in a water bath at 60°C. After filtration, it was vacuum dried at 80°C for 6 hours and then ground through a 200-mesh sieve.
[0034] Furthermore, after adding surface-treated basalt short fibers, the preparation method further includes adding modified polyacrylonitrile short fibers.
[0035] Furthermore, after adding γ-aminopropyltriethoxysilane, the preparation method further includes: adding the layered bimetallic hydroxide and the hindered amine light stabilizer, and continuing to stir for 10 minutes.
[0036] The present invention has the following technical effects:
[0037] This invention utilizes a dual coupling system consisting of diatomaceous earth-loaded titanate coupling agent and γ-aminopropyltriethoxysilane to establish a chemical bridge at the asphalt-aggregate-fiber multiphase interface, effectively preventing interfacial delamination caused by moisture intrusion and enhancing water damage resistance. Steel slag micropowder and nano-paleite are compounded to form a micro-nano multilevel filler, densifying the matrix, increasing modulus, and significantly enhancing high-temperature rutting resistance. Basalt short-cut fibers, after acid etching activation and silane grafting treatment, exhibit strengthened fiber-matrix interfacial bonding, resulting in significant fiber pull-out energy dissipation and bridging crack effects under load, effectively inhibiting low-temperature cracking and fatigue crack propagation. The synergistic effect of all components endows the mixture with excellent high-temperature rutting resistance, low-temperature crack resistance, water damage resistance, and fatigue durability. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0039] In a first aspect, the present invention provides an asphalt mixture, comprising, by weight parts:
[0040] 4.5-6 parts of base asphalt;
[0041] 58-65 parts of coarse aggregate;
[0042] 18-25 parts of fine aggregate;
[0043] 6-10 parts of the first modified filler;
[0044] 3-6 parts of the second modified filler;
[0045] 0.25-0.45 parts of basalt short-cut fibers;
[0046] 0.5-1.2 parts of hydroxyl-terminated liquid nitrile rubber;
[0047] 0.08-0.15 parts of γ-aminopropyltriethoxysilane;
[0048] 4-8 parts of limestone mineral powder;
[0049] The first modified filler is a diatomaceous earth-supported titanate coupling agent, and the titanate coupling agent is isopropyltris(dioctylpyrophosphate) titanate.
[0050] The second modified filler is a composite powder of steel slag micro powder and nano-pachymanite, wherein the steel slag micro powder has a specific surface area of 450-550 m². 2 / kg, wherein the diameter of the nano-pachymanite is 20-40nm and the length is 0.5-5μm, and the mass ratio of the steel slag powder to the nano-pachymanite is 7:3;
[0051] The surface of the basalt short-cut fibers is acid-etched and activated, and then grafted with γ-aminopropyltriethoxysilane. The length of the basalt short-cut fibers is 3-6 mm.
[0052] In some embodiments, the mass ratio of the titanate coupling agent to the diatomaceous earth in the diatomaceous earth-supported titanate coupling agent is (0.15-0.25):1.
[0053] In some embodiments, the first modified filler also includes sodium dodecylbenzenesulfonate at a mass of 0.5% of the total mass of the first modified filler.
[0054] In some embodiments, the coarse aggregate is basalt crushed stone with a particle size ≥ 2.36 mm, and the fine aggregate is manufactured sand with a particle size < 2.36 mm.
[0055] In some embodiments, 0.3-0.8 parts of modified polyacrylonitrile short fibers are also included. The modified polyacrylonitrile short fibers are polyacrylonitrile short fibers that have undergone liquid-phase reduction treatment with hydrazine hydrate. The conditions for liquid-phase reduction treatment with hydrazine hydrate are: hydrazine hydrate mass fraction of 5%-10%, treatment temperature of 70-90℃, treatment time of 2-4 hours, and the length of the polyacrylonitrile short fibers is 2-5 mm, with a single filament diameter ≤10 μm.
[0056] In some embodiments, the mixture further includes 0.1-0.3 parts of a layered bimetallic hydroxide and 0.2-0.6 parts of a hindered amine light stabilizer; the layered bimetallic hydroxide is a magnesium-aluminum type layered bimetallic hydroxide, wherein the molar ratio of Mg to Al is 2:1-3:1; the hindered amine light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0057] Secondly, the present invention also provides a method for preparing the above-mentioned asphalt mixture, comprising the following steps:
[0058] After heating the base asphalt, add hydroxyl-terminated liquid nitrile rubber under stirring conditions and stir until homogeneous to obtain a mixture;
[0059] Add a first modified filler and part of a second modified filler to the mixture, stir evenly, then add γ-aminopropyltriethoxysilane, continue stirring and let stand to obtain modified asphalt binder;
[0060] The coarse aggregate and fine aggregate are dried and heated separately, then mixed evenly, and then the modified asphalt binder is added and mixed to obtain a mixture.
[0061] Add the remaining second modified filler and surface-treated basalt short-cut fibers to the mixture, continue to mix evenly, then add limestone mineral powder and mix evenly to obtain asphalt material;
[0062] The asphalt material is shaped, cooled, and then demolded.
[0063] In some embodiments, the method for preparing the surface-treated basalt chopped fibers is as follows:
[0064] Basalt chopped fibers were immersed in 1 mol / L hydrochloric acid solution for ultrasonic treatment, water washing, and drying. The dried basalt chopped fibers were then immersed in 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution and reacted at 60°C for 2 hours. After washing, the fibers were dried.
[0065] The preparation method of the diatomaceous earth-supported titanate coupling agent is as follows:
[0066] Isopropyl tris(dioctyl pyrophosphate) titanate was dissolved in anhydrous ethanol to prepare a coupling agent solution. The dried diatomaceous earth was added to the coupling agent solution and stirred for 2 hours in a water bath at 60°C. After filtration, it was vacuum dried at 80°C for 6 hours and then ground through a 200-mesh sieve.
[0067] In some embodiments, after adding surface-treated basalt short fibers, the preparation method further includes adding modified polyacrylonitrile short fibers.
[0068] In some embodiments, after adding γ-aminopropyltriethoxysilane, the preparation method further includes: adding the layered bimetallic hydroxide and the hindered amine light stabilizer, and continuing to stir for 10 minutes.
[0069] The following is a detailed explanation using specific embodiments:
[0070] Example 1:
[0071] 1. Raw material composition and specific quality
[0072] Base asphalt: 4.8 kg, using No. 70 road petroleum asphalt.
[0073] Coarse aggregate: 60.0 kg, made of basalt crushed stone with a particle size range of 4.75-13.2 mm.
[0074] Fine aggregate: 20.0kg, made of limestone manufactured sand, with a particle size range of 0-2.36mm and a sand equivalent of not less than 70%.
[0075] Diatomaceous earth loaded with titanate coupling agent: 7.5 kg, wherein the titanate coupling agent is isopropyl tris(dioctyl pyrophosphoryloxy) titanate, the mass ratio of titanate coupling agent to diatomaceous earth is 0.20:1, and the specific surface area of diatomaceous earth ranges from 20 to 25 m². 2 / g, with an average pore size ranging from 7 to 10 nm.
[0076] Composite powder of steel slag micron powder and nano-pachymanite: 4.5 kg, the specific surface area of the steel slag micron powder is 500 m². 2 / kg, the diameter of nano-pachymanite is 25-35nm and the length is 1-3μm, and the mass ratio of steel slag powder to nano-pachymanite is 7:3.
[0077] Basalt chopped fiber: 0.35kg, with a single filament diameter ranging from 12-14μm and a length of 4mm.
[0078] Hydroxyl-terminated liquid nitrile rubber: 0.8 kg, hydroxyl value range of 0.60-0.70 mmol / g, acrylonitrile content of 26%, number average molecular weight of 2800.
[0079] γ-aminopropyltriethoxysilane: 0.12 kg.
[0080] Limestone powder: 6.0 kg, apparent density not less than 2.70 g / cm³ 3 The water content is no more than 0.5%, and the hydrophilicity coefficient is no more than 0.65.
[0081] 2. Pretreatment steps
[0082] (1) Preparation method of surface-treated basalt short fibers:
[0083] Take 0.35 kg of basalt short-cut fibers, immerse them in 1 mol / L hydrochloric acid solution, place them in an ultrasonic cleaner and treat them at 40 kHz ultrasonic power for 30 minutes. Then take out the fibers and rinse them repeatedly with deionized water until the washing solution is neutral. Place the washed fibers in a 105℃ forced-air drying oven and dry them for 2 hours.
[0084] After drying, the fibers were immersed in a 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution and reacted at a constant temperature of 60°C in a water bath for 2 hours. During the reaction, the fibers were stirred with a glass rod every 20 minutes to ensure uniform grafting.
[0085] After the reaction is complete, the fibers are removed and washed three times with anhydrous ethanol. Then, they are dried in a vacuum drying oven at 80°C for 4 hours to obtain surface-treated basalt short fibers, which are then sealed and stored for later use.
[0086] (2) Preparation method of diatomaceous earth-supported titanate coupling agent:
[0087] Dissolve 1.25 kg of isopropyl tris(dioctyl pyrophosphoryloxy) titanate in 8.0 L of anhydrous ethanol and stir at 300 rpm with a mechanical stirrer until completely dissolved to prepare a coupling agent solution.
[0088] Take 6.25 kg of dried diatomaceous earth and slowly add it to the above coupling agent solution under continuous stirring. Stir at a constant temperature of 60°C for 2 hours, keeping the stirring speed at 350 rpm.
[0089] After the reaction was completed, the filter cake was collected by vacuum filtration using a Buchner funnel and washed twice with anhydrous ethanol. The washed filter cake was then dried in a vacuum drying oven at 80°C for 6 hours.
[0090] The dried product is ground in a mortar and pestle and passed through a 200-mesh standard sieve. The material passing through the sieve is the first modified filler, which is then stored in a sealed bag to prevent moisture.
[0091] (3) Premixing of the second modified filler:
[0092] Take 3.15 kg of steel slag powder and 1.35 kg of nano palygorskite, put them into a high-speed mixer, and mix them at a stirring speed of 800 rpm for 15 minutes to ensure that the two powders are fully mixed and uniform. Discharge the mixture for later use.
[0093] 3. Preparation steps of asphalt mixture
[0094] (1) Preparation of modified asphalt binder:
[0095] 4.8 kg of base asphalt was put into an asphalt heating tank and heated to 160°C. After the asphalt was completely fluid, 0.8 kg of hydroxyl-terminated liquid nitrile rubber was slowly added while the mechanical stirring speed was 400 rpm. The temperature was maintained at 160°C and the mixture was stirred continuously for 30 minutes to make the hydroxyl-terminated liquid nitrile rubber evenly dispersed in the asphalt, thus obtaining mixture A.
[0096] Add 7.5 kg of diatomaceous earth-supported titanate coupling agent and 2.25 kg of composite powder of steel slag micro powder and nano palygorskite to the above mixture A, increase the stirring speed to 500 rpm, maintain the temperature at 160℃, and continue stirring for 20 minutes.
[0097] Then slowly add 0.12 kg of γ-aminopropyltriethoxysilane, maintaining the same stirring speed and temperature, and continue stirring for 10 minutes.
[0098] After mixing, reduce the mixing speed to 200 rpm, stop heating, and allow the material to cool naturally to 140°C. Then, keep it at 140°C for 20 minutes to obtain the modified asphalt binder, which is ready for use.
[0099] (2) Pretreatment of aggregates:
[0100] 60.0 kg of basalt crushed stone and 20.0 kg of limestone manufactured sand were placed in a forced-air drying oven and dried at 175℃ to constant weight.
[0101] Take out the dried coarse and fine aggregates and put them into the asphalt mixing pot that has been preheated to 170℃ while they are still hot, and keep the aggregate temperature within the range of 170±5℃.
[0102] (3) Mixing process:
[0103] Start the mixing pot and dry mix the preheated coarse and fine aggregates for 15 seconds to ensure they are evenly mixed.
[0104] Then, the modified asphalt binder is added to the mixing pot, and wet mixing is carried out at a mixing temperature of 165℃ for 45 seconds to ensure that the asphalt fully coats the surface of the aggregate, thus obtaining mixture B.
[0105] (4) Add the remaining second modified filler, basalt short-cut fibers and limestone mineral powder:
[0106] Add 2.25 kg of composite powder of steel slag micro powder and nano palygorskite and 0.35 kg of surface-treated basalt short-cut fibers to the above mixture B, and continue mixing for 30 seconds at a mixing temperature of 165℃.
[0107] Then add 6.0 kg of limestone powder and continue mixing for 30 seconds at the same temperature to ensure that the limestone powder is evenly dispersed in the mixture, thus obtaining asphalt material C.
[0108] (5) Molding and demolding:
[0109] The well-mixed asphalt material C was immediately loaded into a rut slab mold that had been preheated to 150°C, and then rolled and shaped using a roller roller forming machine, with 12 round trips set for the rolling process.
[0110] After molding, the specimens, along with the molds, were allowed to cool naturally at room temperature for 24 hours. Then, they were demolded using a demolding device to obtain asphalt mixture rutting slab specimens.
[0111] Example 2
[0112] 1. Raw material composition and specific quality
[0113] Base asphalt: 5.5 kg, using No. 90 road petroleum asphalt.
[0114] Coarse aggregate: 63.0 kg, made of basalt crushed stone with a particle size range of 4.75-16 mm.
[0115] Fine aggregate: 22.0kg, made of manufactured granite sand, with a particle size range of 0-2.36mm and a sand equivalent of not less than 68%.
[0116] Diatomaceous earth loaded with titanate coupling agent: 9.0 kg, the titanate coupling agent is isopropyl tris(dioctyl pyrophosphate) titanate, the mass ratio of titanate coupling agent to diatomaceous earth is 0.22:1, and the specific surface area of diatomaceous earth ranges from 25 to 30 m². 2 / g.
[0117] Composite powder of steel slag micron powder and nano-pachymanite: 5.0 kg, the specific surface area of the steel slag micron powder is 520 m². 2 / kg, the diameter of nano-pachymanite is 30-40nm and the length is 2-4μm, and the mass ratio of steel slag powder to nano-pachymanite is 7:3.
[0118] Basalt chopped fiber: 0.42kg, with a single filament diameter ranging from 14-16μm and a length of 5mm.
[0119] Hydroxyl-terminated liquid nitrile rubber: 1.0 kg, hydroxyl value range of 0.55-0.65 mmol / g, acrylonitrile content of 30%, number average molecular weight of 3200.
[0120] γ-aminopropyltriethoxysilane: 0.14 kg.
[0121] Limestone powder: 7.0 kg, apparent density not less than 2.72 g / cm³ 3 The water content is no more than 0.4%, and the hydrophilicity coefficient is no more than 0.60.
[0122] Modified polyacrylonitrile short fiber: 0.5 kg. This modified polyacrylonitrile short fiber is a polyacrylonitrile short fiber that has been treated with hydrazine hydrate liquid phase reduction. The original length of the polyacrylonitrile short fiber is 3 mm and the diameter of the single filament is 8 μm. The specific conditions for the hydrazine hydrate liquid phase reduction treatment are: hydrazine hydrate mass fraction of 8%, treatment temperature of 80℃, and treatment time of 3 hours.
[0123] Layered bimetallic hydroxide: 0.2 kg. This layered bimetallic hydroxide is a magnesium-aluminum type layered bimetallic hydroxide, wherein the molar ratio of Mg to Al is 2.5:1.
[0124] Hindered amine light stabilizer: 0.4 kg, which is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0125] 2. Pretreatment steps
[0126] (1) Preparation method of surface-treated basalt short fibers:
[0127] Take 0.42 kg of basalt short-cut fibers, immerse them in 1 mol / L hydrochloric acid solution, treat them with 40 kHz ultrasonic power for 30 minutes, then rinse them repeatedly with deionized water until neutral, and dry them at 105℃ for 2 hours.
[0128] After drying, the fibers are immersed in a 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution (solvent is 95% aqueous ethanol) and reacted in a water bath at 60°C for 2 hours, with stirring every 20 minutes during the reaction.
[0129] After the reaction is complete, wash three times with anhydrous ethanol, dry under vacuum at 80°C for 4 hours, and seal for later use.
[0130] (2) Preparation method of diatomaceous earth-supported titanate coupling agent:
[0131] Dissolve 1.62 kg of isopropyl tris(dioctyl pyrophosphate) titanate in 10.0 L of anhydrous ethanol and stir at 300 rpm with a mechanical stirrer until completely dissolved to prepare a coupling agent solution.
[0132] Take 7.38 kg of dried diatomaceous earth and slowly add it to the above coupling agent solution under continuous stirring. At the same time, add 0.045 kg of sodium dodecylbenzenesulfonate as a dispersing agent. Stir at a constant temperature of 60°C for 2 hours under a water bath with a stirring speed of 350 rpm.
[0133] After the reaction was completed, the filter cake was collected by suction filtration using a Buchner funnel and washed three times with anhydrous ethanol.
[0134] The washed filter cake was placed in an 80℃ vacuum drying oven and dried for 6 hours. The dried product was ground in a mortar and pestle and passed through a 200-mesh standard sieve. The material passing through the sieve was collected as the first modified filler and stored in a sealed bag to prevent moisture.
[0135] (3) Premixing of the second modified filler:
[0136] Take 3.50 kg of steel slag powder and 1.50 kg of nano palygorskite, put them into a high-speed mixer, stir at 900 rpm for 20 minutes, and discharge the mixture for later use.
[0137] (4) Pretreatment of modified polyacrylonitrile short fibers:
[0138] Take 0.5 kg of polyacrylonitrile short fibers, immerse them in an 8% (w / w) hydrazine hydrate aqueous solution, and treat them in an 80°C water bath for 3 hours.
[0139] After processing, the polyacrylonitrile short fibers are removed, repeatedly washed with deionized water until the washing solution is neutral, and then dried in a vacuum drying oven at 60°C for 6 hours to obtain modified polyacrylonitrile short fibers, which are then sealed for later use.
[0140] 3. Preparation steps of asphalt mixture
[0141] (1) Preparation of modified asphalt binder:
[0142] Add 5.5 kg of base asphalt to an asphalt heating tank and heat it to 165 ± 5 °C. After the asphalt is completely melted, add 1.0 kg of hydroxyl-terminated liquid nitrile rubber while stirring at 450 rpm. Maintain the temperature at 165 °C and continue stirring for 35 minutes to obtain a homogeneous mixture A.
[0143] Add 9.0 kg of diatomaceous earth-supported titanate coupling agent and 2.5 kg of composite powder of steel slag micro powder and nano palygorskite to mixture A, increase the stirring speed to 550 rpm, maintain the temperature at 165℃, and continue stirring for 25 minutes.
[0144] Then slowly add 0.14 kg of γ-aminopropyltriethoxysilane, and continue stirring for 10 minutes while maintaining the same stirring conditions.
[0145] After mixing, reduce the mixing speed to 250 rpm, stop heating, and allow the material to cool naturally to 145°C. Then, keep it at 145°C for 25 minutes to obtain the modified asphalt binder.
[0146] (2) Pretreatment of aggregates:
[0147] 63.0 kg of coarse aggregate and 22.0 kg of fine aggregate were placed in a forced-air drying oven and dried at 180°C to constant weight. After being taken out, they were put into an asphalt mixing pot that had been preheated to 175°C while still hot, and the aggregate temperature was kept within the range of 175°C.
[0148] (3) Mixing process:
[0149] Start the mixing pot and dry mix the preheated coarse and fine aggregates for 20 seconds. Then add the modified asphalt binder and wet mix at a mixing temperature of 170℃ for 50 seconds to obtain mixture B.
[0150] (4) Add 2.5 kg of composite powder of steel slag micro powder and nano palygorskite, 0.42 kg of basalt short fiber and 0.5 kg of modified polyacrylonitrile short fiber to mixture B, and continue mixing for 35 seconds at a mixing temperature of 170℃. Then add all 7.0 kg of limestone mineral powder, and continue mixing for 40 seconds at the same temperature to obtain asphalt material C.
[0151] (5) Molding and demolding:
[0152] The well-mixed asphalt material C was immediately loaded into a rut slab mold that had been preheated to 155°C, and then rolled and shaped using a roller roller forming machine, with 12 round trips set for the rolling process.
[0153] After molding, the specimens, along with the molds, were allowed to cool naturally at room temperature for 24 hours. Then, they were demolded using a demolding device to obtain asphalt mixture rutting slab specimens.
[0154] Example 3
[0155] 1. Raw material composition and specific quality
[0156] Base asphalt: 5.0 kg.
[0157] Coarse aggregate: 61.0 kg, made of basalt crushed stone with a particle size range of 4.75-13.2 mm.
[0158] Fine aggregate: 19.0kg, made of basalt manufactured sand, with a particle size range of 0-2.36mm and a sand equivalent of not less than 72%.
[0159] Diatomaceous earth loaded with titanate coupling agent: 8.0 kg, the titanate coupling agent is isopropyl tris(dioctyl pyrophosphate) titanate, the mass ratio of titanate coupling agent to diatomaceous earth is 0.18:1, and the specific surface area of diatomaceous earth ranges from 20 to 25 m². 2 / g.
[0160] Composite powder of steel slag micron powder and nano-pachymanite: 3.5 kg, the specific surface area of the steel slag micron powder is 460 m². 2 / kg, the diameter of nano-pachymanite is 20-30nm and the length is 0.5-2μm, and the mass ratio of steel slag powder to nano-pachymanite is 7:3.
[0161] Basalt chopped fiber: 0.28kg, with a single filament diameter ranging from 11 to 13μm and a length of 6mm.
[0162] Hydroxyl-terminated liquid nitrile rubber: 0.6 kg, hydroxyl value range of 0.65-0.75 mmol / g, acrylonitrile content of 22%, number average molecular weight of 2500.
[0163] γ-aminopropyltriethoxysilane: 0.10 kg.
[0164] Limestone powder: 5.0 kg, apparent density not less than 2.68 g / cm³ 3 The water content is no more than 0.5%, and the hydrophilicity coefficient is no more than 0.65.
[0165] Modified polyacrylonitrile short fiber: 0.35 kg. This modified polyacrylonitrile short fiber is a polyacrylonitrile short fiber that has been treated with hydrazine hydrate liquid phase reduction. The original length of the polyacrylonitrile short fiber is 4 mm and the diameter of the single filament is 9 μm. The specific conditions for the hydrazine hydrate liquid phase reduction treatment are: hydrazine hydrate mass fraction of 6%, treatment temperature of 75℃, and treatment time of 4 hours.
[0166] Layered bimetallic hydroxide: 0.15 kg. This layered bimetallic hydroxide is a magnesium-aluminum type layered bimetallic hydroxide, wherein the molar ratio of Mg to Al is 2.8:1.
[0167] Hindered amine light stabilizer: 0.25 kg, which is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0168] 2. Pretreatment steps
[0169] (1) Preparation method of surface-treated basalt short fibers:
[0170] Take 0.28 kg of basalt short-cut fibers (6 mm in length), immerse them in 1 mol / L hydrochloric acid solution, treat them with 40 kHz ultrasonic power for 30 minutes, then rinse them repeatedly with deionized water until neutral, and dry them at 105 ℃ for 2 hours.
[0171] After drying, the fibers are immersed in a 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution and reacted in a water bath at 60°C for 2 hours, with stirring every 20 minutes during the reaction.
[0172] After the reaction is complete, wash three times with anhydrous ethanol, dry under vacuum at 80°C for 4 hours, and seal for later use.
[0173] (2) Preparation method of diatomaceous earth supported titanate coupling agent (i.e., the first modified filler):
[0174] Dissolve 1.22 kg of isopropyl tris(dioctyl pyrophosphate) titanate in 7.5 L of anhydrous ethanol and stir with a mechanical stirrer at 300 rpm until completely dissolved to prepare a coupling agent solution.
[0175] Take 6.78 kg of dried diatomaceous earth and slowly add it to the above coupling agent solution under continuous stirring. At the same time, add 0.040 kg of sodium dodecylbenzenesulfonate as a dispersing agent. Stir at a constant temperature of 60°C for 2 hours under a water bath with a stirring speed of 350 rpm.
[0176] After the reaction was completed, the filter cake was collected by suction filtration using a Buchner funnel and washed three times with anhydrous ethanol.
[0177] The washed filter cake was placed in an 80℃ vacuum drying oven and dried for 6 hours. The dried product was ground in a mortar and pestle and passed through a 200-mesh standard sieve. The material passing through the sieve was collected as the first modified filler and stored in a sealed bag to prevent moisture.
[0178] (3) Premixing of the second modified filler:
[0179] Take 2.45 kg of steel slag powder and 1.05 kg of nano palygorskite, put them into a high-speed mixer, stir at 750 rpm for 18 minutes, and discharge the mixture for later use.
[0180] (4) Pretreatment of modified polyacrylonitrile short fibers:
[0181] Take 0.35 kg of polyacrylonitrile short fibers and immerse them in a 6% (w / w) hydrazine hydrate aqueous solution. Treat the solution in a 75°C water bath for 4 hours. After treatment, remove the fibers and wash them repeatedly with deionized water until the washing solution is neutral. Then, dry them in a 60°C vacuum drying oven for 6 hours to obtain modified polyacrylonitrile short fibers. Seal and store for later use.
[0182] 3. Preparation steps of asphalt mixture
[0183] (1) Preparation of modified asphalt binder:
[0184] Add 5.0 kg of base asphalt to an asphalt heating tank and heat it to 160 ± 5 °C. After the asphalt is completely melted, add 0.6 kg of hydroxyl-terminated liquid nitrile rubber while stirring at 400 rpm. Maintain the temperature at 160 °C and continue stirring for 40 minutes to obtain a homogeneous mixture A.
[0185] Add 8.0 kg of diatomaceous earth-supported titanate coupling agent and 1.75 kg of composite powder of steel slag micro powder and nano palygorskite to mixture A. Increase the stirring speed to 500 rpm, maintain the temperature at 160℃, and continue stirring for 20 minutes.
[0186] Then slowly add 0.10 kg of γ-aminopropyltriethoxysilane, and continue stirring for 10 minutes while maintaining the same stirring conditions.
[0187] Then add 0.15 kg of layered bimetallic hydroxide and 0.25 kg of hindered amine light stabilizer, and continue stirring for 10 minutes at the same stirring speed and temperature.
[0188] After mixing, reduce the mixing speed to 250 rpm, stop heating, and allow the material to cool naturally to 145°C. Then, keep it at 145°C for 30 minutes to obtain the modified asphalt binder.
[0189] (2) Pretreatment of aggregates:
[0190] 61.0 kg of basalt crushed stone and 19.0 kg of basalt manufactured sand were placed in a forced-air drying oven and dried at 175°C to constant weight. After being taken out, they were put into an asphalt mixing pot that had been preheated to 170°C while still hot, and the aggregate temperature was kept within the range of 170°C.
[0191] (3) Mixing process:
[0192] Start the mixing pot and dry mix the preheated coarse and fine aggregates for 15 seconds. Then add the modified asphalt binder and wet mix at a mixing temperature of 165℃ for 55 seconds to obtain mixture B.
[0193] (4) Add 1.75 kg of composite powder of steel slag micro powder and nano palygorskite, 0.28 kg of basalt short fiber and 0.35 kg of modified polyacrylonitrile short fiber to mixture B, and continue mixing for 35 seconds at a mixing temperature of 165℃.
[0194] Then add 5.0 kg of limestone powder and continue mixing at the same temperature for 45 seconds to obtain asphalt material C.
[0195] (5) Molding and demolding:
[0196] Asphalt material C was loaded into a rut slab mold preheated to 150°C and compacted using a roller mill, with 12 round trips set for each compaction.
[0197] After molding, the specimens, along with the mold, were allowed to cool naturally at room temperature for 48 hours. Then, they were demolded using a demolding device to obtain asphalt mixture rutting slab specimens for subsequent cutting and performance testing.
[0198] Experimental Example 1: Verification of the Road Performance of Asphalt Mixtures
[0199] 1. Preparation of experimental specimens
[0200] 1.1 Specimen Numbering and Grouping
[0201] The asphalt mixture specimens prepared in Examples 1, 2, and 3 were numbered S-1, S-2, and S-3, respectively. A control example, S-0, was prepared using ordinary No. 70 base asphalt according to the AC-13 gradation for performance comparison.
[0202] 1.2 Number of Specimens
[0203] For each embodiment and control example, a corresponding number of parallel specimens were prepared according to the requirements of each test item, specifically:
[0204] Rutting test: Three rutting slab specimens were prepared for each group;
[0205] Low-temperature bending test: 6 small beam specimens were cut from the rutted slab for each group;
[0206] Immersion Marshall test: Eight standard Marshall specimens were prepared for each group, four of which were used for the immersion test and four were used as controls;
[0207] Freeze-thaw splitting test: 6 standard Marshall specimens were prepared for each group, of which 3 were used for freeze-thaw cycles and 3 were used as controls;
[0208] Four-point bending fatigue test: 6 small beam specimens were prepared for each group.
[0209] 2. Experimental Items and Methods
[0210] 2.1 High Temperature Stability Test – Rutting Test
[0211] Experimental steps:
[0212] After the rutted plate specimens of Examples 1, 2, 3 and Control Example S-0 were placed at room temperature for 24 hours, they were placed in a 60°C constant temperature oven for 5 hours to ensure that the internal temperature of the specimens reached 60°C uniformly.
[0213] Remove the specimen from the constant temperature chamber and quickly place it on the test bench of the rutting test machine. Adjust the position of the specimen so that it is directly below the loading wheel.
[0214] Start the rutting test machine, set the test wheel pressure to 0.7 MPa, the travel speed to 42 times / minute, and the test temperature to 60℃.
[0215] The loading device is activated, causing the test wheel to move repeatedly on the surface of the specimen. At the same time, the displacement sensor and data acquisition system are turned on to record the deformation of the specimen surface in real time.
[0216] The test lasted for 60 minutes, and the deformation value was automatically recorded every 10 seconds.
[0217] After the test, the specimen was removed and the rut depth and surface condition of the specimen were observed.
[0218] Based on the collected deformation data, the dynamic stability of the specimens was calculated in the time interval of 45 to 60 minutes, and the average dynamic stability of the three specimens in each group was taken as the final result.
[0219] The final experimental results are shown in Table 1 below.
[0220] Table 1 Results of rutting test
[0221]
[0222] 2.2 Low-Temperature Crack Resistance Test – Low-Temperature Bending Test
[0223] From the rutted plates of Examples 1, 2, 3 and Comparative Example S-0, small beam specimens with a length of 250 mm, a width of 35 mm and a height of 30 mm were cut using a double-sided saw. Six small beams were cut from each rutted plate.
[0224] The cut beam specimens were placed in a -10℃ low-temperature constant temperature chamber for 4 hours to ensure that the internal temperature of the specimens reached a uniform -10±0.5℃.
[0225] Remove the specimen from the constant temperature chamber and quickly install it onto the three-point bending fixture of the universal testing machine. Set the span to 200 mm and the loading rate to 50 mm / min. Install a displacement extensometer at the mid-span of the specimen to accurately measure the mid-span deflection.
[0226] Start the testing machine to apply load, and simultaneously start the data acquisition system to record the load and mid-span deflection data until the specimen fails. Record the failure load and mid-span failure deflection of the specimen.
[0227] After the test, the bending failure strain and bending stiffness modulus of the specimen were calculated.
[0228] The final experimental results are shown in Table 2 below.
[0229] Table 2 Results of Low Temperature Bending Test
[0230]
[0231] 3.3 Water stability test – Immersion Marshall test
[0232] The standard Marshall specimens from Examples 1, 2, 3, and Control Example S-0 were divided into two groups of four specimens each. The first group was the control specimens, and the second group was the water-immersed specimens.
[0233] Treatment of control specimens: The first group of specimens was placed in a 60℃ constant temperature water bath for 30 minutes, and then immediately taken out for Marshall stability test.
[0234] Treatment of water-immersed specimens: The second group of specimens were placed in a 60℃ constant temperature water bath for 48 hours and then immediately subjected to a Marshall stability test.
[0235] Marshall stability test procedure: Remove the specimen from the water bath after the heat preservation is completed, wipe off the surface moisture, and immediately install it between the upper and lower pressure heads of the Marshall stability tester. Set the loading rate to 50 mm / min, start the tester to load until the specimen fails, record the maximum failure load, and record the flow value of the specimen at the same time. Take the average value of 4 specimens in each group to calculate the residual stability.
[0236] The final experimental results are shown in Table 3 below.
[0237] Table 3 Results of the Marshall Immersion Test
[0238]
[0239] 3.4 Water stability test – freeze-thaw splitting test
[0240] The standard Marshall specimens from Examples 1, 2, 3, and Control Example S-0 were divided into two groups of three specimens each. The first group consisted of control specimens, and the second group consisted of freeze-thaw specimens.
[0241] Treatment of control specimens: The first group of specimens were placed at room temperature for 24 hours, then placed in a constant temperature water bath at 25℃ for 2 hours, and then subjected to splitting test.
[0242] Treatment of freeze-thaw specimens: The second group of specimens was placed in a vacuum saturation apparatus and maintained at a vacuum of 98.3 kPa for 15 minutes. Then, the pressure was restored to normal, and the specimens were immersed in water for 30 minutes, until the saturation rate reached 70%–80%. The saturated specimens were then removed, tightly wrapped in plastic film, and frozen in a -18°C freezer for 16 hours. After freezing, the specimens were removed and immediately thawed in a 60°C constant temperature water bath for 24 hours. After thawing, the specimens were placed in a 25°C constant temperature water bath for 2 hours, and then subjected to a splitting crack test.
[0243] Splitting test procedure: Remove the specimen from the water bath after the insulation is completed, wipe off the surface moisture, install it in the splitting test fixture, set the loading rate to 50 mm / min, start the universal testing machine to load until the specimen fails, record the maximum failure load, and take the average value of 3 specimens in each group to calculate the freeze-thaw splitting tensile strength ratio.
[0244] The final experimental results are shown in Table 4 below.
[0245] Table 4 Results of freeze-thaw splitting test
[0246]
[0247] 3.5 Fatigue resistance test – Four-point bending fatigue test
[0248] From the rutted plates of Examples 1, 2, 3 and Comparative Example S-0, small beam specimens with a length of 300 mm, a width of 50 mm and a height of 50 mm were cut using a double-sided saw. Six small beams were cut from each rutted plate.
[0249] The cut beam specimens were placed in a 15℃ constant temperature chamber for 4 hours to ensure that the internal temperature of the specimens reached a uniform 15±0.5℃.
[0250] Remove the specimen from the constant temperature chamber and quickly install it on the fixture of the four-point bending fatigue testing machine. Set the span to 356 mm, the loading frequency to 10 Hz, and the strain control mode to control the strain to 600 με.
[0251] The testing machine is started to apply load, and the data acquisition system is activated simultaneously to record load and displacement data in real time. When the stiffness modulus of the specimen drops to 50% of the initial stiffness modulus, the specimen is deemed to have reached fatigue failure. The number of load cycles experienced at this point is recorded, which is the fatigue life of the specimen.
[0252] The average fatigue life of each group of 6 specimens was taken as the final result, and the growth rate of fatigue life of each example specimen relative to the fatigue life of the control example specimen was calculated.
[0253] The final results are shown in Table 5 below.
[0254] Table 5 Results of Four-Point Bending Fatigue Test
[0255]
[0256] As can be seen from the above experimental results, the dynamic stability of each embodiment of the present invention reached 1125 cycles / mm, 1658 cycles / mm, and 1537 cycles / mm, respectively, which is significantly improved compared with the control example (759 cycles / mm). Among them, Examples 2 and 3 meet the technical requirements of heavy traffic highways. The bending failure strain reached 2982με, 3444με, and 3276με, respectively, which are improved by 36.5%, 57.7%, and 50.0% compared with the control example (2184με), indicating that the present invention performs excellently in both high-temperature rutting resistance and low-temperature crack resistance. In terms of water stability, the residual stability reached 86.3%, 92.7%, and 90.5%, respectively, and the freeze-thaw splitting strength ratio reached 82.5%, 89.6%, and 87.3%, respectively, all significantly higher than the standard requirements, demonstrating outstanding resistance to water damage. The fatigue life reached 52,370, 87,250 and 78,630 cycles respectively, which were 84.0%, 206.6% and 176.3% higher than the control, respectively, and the long-term durability was significantly enhanced.
[0257] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the present invention.
Claims
1. An asphalt mixture, characterized in that, By weight, it includes: 4.5-6 parts of base asphalt; 58-65 parts of coarse aggregate; 18-25 parts of fine aggregate; 6-10 parts of the first modified filler; 3-6 parts of the second modified filler; 0.25-0.45 parts of basalt short-cut fibers; 0.5-1.2 parts of hydroxyl-terminated liquid nitrile rubber; 0.08-0.15 parts of γ-aminopropyltriethoxysilane; 4-8 parts of limestone mineral powder; The first modified filler is a diatomaceous earth-supported titanate coupling agent, and the titanate coupling agent is isopropyltris(dioctylpyrophosphate) titanate. The second modified filler is a composite powder of steel slag micro powder and nano-pachymanite, wherein the steel slag micro powder has a specific surface area of 450-550 m². 2 / kg, wherein the diameter of the nano-pachymanite is 20-40nm and the length is 0.5-5μm, and the mass ratio of the steel slag powder to the nano-pachymanite is 7:3; The surface of the basalt short-cut fibers is acid-etched and activated, and then grafted with γ-aminopropyltriethoxysilane. The length of the basalt short-cut fibers is 3-6 mm.
2. The asphalt mixture according to claim 1, characterized in that, In the diatomaceous earth-supported titanate coupling agent, the mass ratio of the titanate coupling agent to the diatomaceous earth is (0.15-0.25):
1.
3. The asphalt mixture according to claim 1, characterized in that, The first modified filler also includes sodium dodecylbenzenesulfonate, which accounts for 0.5% of the total mass of the first modified filler.
4. The asphalt mixture according to claim 1, characterized in that, The coarse aggregate is basalt crushed stone with a particle size ≥ 2.36 mm, and the fine aggregate is manufactured sand with a particle size < 2.36 mm.
5. An asphalt mixture according to claim 1, characterized in that, It also includes 0.3-0.8 parts of modified polyacrylonitrile short fibers, wherein the modified polyacrylonitrile short fibers are polyacrylonitrile short fibers after being treated with hydrazine hydrate liquid phase reduction. The conditions for the hydrazine hydrate liquid phase reduction treatment are: hydrazine hydrate mass fraction of 5%-10%, treatment temperature of 70-90℃, treatment time of 2-4 hours, and the length of the polyacrylonitrile short fibers is 2-5mm, and the diameter of the single filament is ≤10μm.
6. An asphalt mixture according to claim 1, characterized in that, It also includes 0.1-0.3 parts of a layered bimetallic hydroxide and 0.2-0.6 parts of a hindered amine light stabilizer; the layered bimetallic hydroxide is a magnesium-aluminum type layered bimetallic hydroxide, wherein the molar ratio of Mg to Al is 2:1-3:1; the hindered amine light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
7. A method for preparing asphalt mixture as described in claim 1, characterized in that, Includes the following steps: After heating the base asphalt, add hydroxyl-terminated liquid nitrile rubber under stirring conditions and stir until homogeneous to obtain a mixture; Add a first modified filler and part of a second modified filler to the mixture, stir evenly, then add γ-aminopropyltriethoxysilane, continue stirring and let stand to obtain modified asphalt binder; The coarse aggregate and fine aggregate are dried and heated separately, then mixed evenly, and then the modified asphalt binder is added and mixed to obtain a mixture. Add the remaining second modified filler and surface-treated basalt short-cut fibers to the mixture, continue to mix evenly, then add limestone mineral powder and mix evenly to obtain asphalt material; The asphalt material is shaped, cooled, and then demolded.
8. The preparation method according to claim 7, characterized in that, The method for preparing the surface-treated basalt short-cut fibers is as follows: Basalt chopped fibers were immersed in 1 mol / L hydrochloric acid solution for ultrasonic treatment, water washing, and drying. The dried basalt chopped fibers were then immersed in 1% (w / w) γ-aminopropyltriethoxysilane ethanol solution and reacted at 60°C for 2 hours. After washing, the fibers were dried. The preparation method of the diatomaceous earth-supported titanate coupling agent is as follows: Isopropyl tris(dioctyl pyrophosphate) titanate was dissolved in anhydrous ethanol to prepare a coupling agent solution. The dried diatomaceous earth was added to the coupling agent solution and stirred for 2 hours in a water bath at 60°C. After filtration, it was vacuum dried at 80°C for 6 hours and then ground through a 200-mesh sieve.
9. The preparation method according to claim 7, characterized in that, After adding surface-treated basalt short fibers, the preparation method further includes adding modified polyacrylonitrile short fibers.
10. The preparation method according to claim 7, characterized in that, After adding γ-aminopropyltriethoxysilane, the preparation method further includes: adding layered bimetallic hydroxide and hindered amine light stabilizer, and continuing to stir for 10 minutes.
Citation Information
Patent Citations
Self-adhesive waterproof roll cementing material and waterproof roll prepared from same
CN114644903A
Asphalt mixture based on desulfurized rubber powder-nano palygorskite-steel slag powder composite modification and preparation method thereof
CN119176691A